IPTEKS BAGI MASYARAKAT KERAJINAN BATIK DENGAN PEWARNA ALAMI DI KECAMATAN SUSUKAN KABUPATEN BANJARNEGARA - Barni; Sarno; Siti Munfiah (Jurnal Ilmiah Medsains, 2018)
Batik craft in Banjarnegara Regency is one of superior product with Gumelem Kulon Village, Gumelem Wetan and Penetan Village Wetan, Susukan Sub-district as its center. There are 59 UKM batik tulis and 11 UKM batik cap in Susukan. UKM is spread in Gumelem Wetan Village 26 UKM, Gumelem Kulon Village 29 UKM, Village Penangkusan Wetan 11 UKM, Kulon 2 UKM and Susukan 2 UKM. The use of natural dyes in batik business become environmentally friendly business potential. Batik UKM in Kecamatan Susukan engaged in batik activities with natural dye there are two UKM that using natural dyes is Giri Alam and Prana Mukti. Both UKM began the production of batik tulis with natural dyes since2015. The purpose of this community service activities was to help batik craftsmen in improving their income and welfare with a healthy production process and environmentally friendly. This activity uses socialization of natural dyes based on local potential, health and safety socialization in batik process, business management and production assistance activities and advisory activities for the application of liquid waste processing technology. The result of this activity are innovation of batik cap product with natural dye, method of application of wastewater treatment technology, metod of application of electric stove technology for melt wax, community empowerment model by giving priority to safety and hearlth of batik craftsmen group.